2014
DOI: 10.1007/s40261-014-0260-8
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of Miglitol and Anagliptin on Insulin-Treated Type 2 Diabetes Mellitus: A Case Study

Abstract: The aim of this case study was to examine the efficacy of a dipeptidyl peptidase-4 inhibitor (anagliptin) and an α-glucosidase inhibitor (miglitol) when added to ongoing insulin treatment in patients with type 2 diabetes mellitus. Continuous glucose monitoring was performed in four Japanese insulin-treated inpatients with type 2 diabetes. Baseline data were collected on day 1. Miglitol was administered on days 2 and 3. On day 4, miglitol and anagliptin were coadministered before breakfast. On days 1, 3, and 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…Also, metformin has been proposed to increase GLP-1 secretion via modulation of bile acids [35]; inhibitory effect of metformin on bile acid reabsorption increases the luminal concentration of bile acids and stimulates Takeda G-protein receptor 5 (TGR5) on enteroendocrine L-cells, leading to increased GLP-1 secretion. Previous studies with a small number of participants have demonstrated insignificant changes in glucagon secretion after short-term treatment of α-glucosidase inhibitors [28293036]. However, in our study, the glucagon levels were suppressed after acarbose add-on therapy in the Met+Sita+Acarb group.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Also, metformin has been proposed to increase GLP-1 secretion via modulation of bile acids [35]; inhibitory effect of metformin on bile acid reabsorption increases the luminal concentration of bile acids and stimulates Takeda G-protein receptor 5 (TGR5) on enteroendocrine L-cells, leading to increased GLP-1 secretion. Previous studies with a small number of participants have demonstrated insignificant changes in glucagon secretion after short-term treatment of α-glucosidase inhibitors [28293036]. However, in our study, the glucagon levels were suppressed after acarbose add-on therapy in the Met+Sita+Acarb group.…”
Section: Discussioncontrasting
confidence: 81%
“…A single administration or a 2-week treatment of acarbose failed to demonstrate significant changes in the plasma glucagon level during MTT in the subjects with T2DM [2829]. In a report by Kishimoto and Noda [30], the short-term co-administration of α-glucosidase inhibitor (miglitol) and DPP4-inhibitor (anagliptin) showed a tendency for suppressed glucagon secretion in four patients. Theoretically, GLP-1 reduces glucose levels through its potent insulinotropic action as well as by suppressing glucagon secretion [31].…”
Section: Discussionmentioning
confidence: 99%
“…For example, H4 changed its position nearly 90°, which lead to three H-bonds interactions between H4, O4 and Gln45, Tyr452 and His148 (Table 4). Actually, multiple hydroxyl groups played a critical role in the stabilization of the miglitol at the catalytic sites of β-glucosidases [46][47][48][49] .…”
Section: Geometrical Conformation Analysis Of Docking Moleculesmentioning
confidence: 99%